Factors associated with unfavorable outcome of tuberculosis treatment in people deprived of liberty: a systematic review - Nanci Michele Saita; Rubia Laine de Paula Andrade; Pedro Augusto Bossonario; Rafaele Oliveira Bonfim; Paula Hino; Aline Aparecida Monroe (SciELO, 2021)
ABSTRACT Objective: to analyze factors associated with unfavorable outcome of tuberculosis treatment in people deprived of liberty. Method: systematic review, carried out in March 2021 in seven databases, with no delimitation of period of publication. The selection process of publications and data extraction was carried out by two independent reviewers. Results: a total of 1,448 publications was identified and nine were included in the study. Unfavorable outcome was higher among those who were men; had low level of education; were living in a rural area before detention; had longer prison time; received occasional visits; had been transferred between prisons; with no sputum smear microscopy or with a positive result at the diagnosis; with no follow-up sputum smear microscopy, previous history of tuberculosis; having both clinical forms of the disease, HIV/AIDS; alcoholics; smokers; low body weight; and self-administered treatment. Treatment default was associated with young people and death with older people. Conclusion: prison health managers and professionals are expected to establish mechanisms of surveillance and health actions innovation aimed at the population deprived of liberty, making efforts to reduce the unfavorable outcomes of tuberculosis treatment.